Unraveling Admixture, Inbreeding, and Recent Selection Signatures in West African Indigenous Cattle Populations in Benin - Vanvanhossou, Sèyi Fridaïus Ulrich; Yin, Tong; Scheper, Carsten; Fries, Ruedi; Dossa, Luc Hippolyte; König, Sven (Frontiers in Genetics, 2021)
The Dwarf Lagune and the Savannah Somba cattle in Benin are typical representatives of the endangered West-African indigenous Shorthorn taurine. The Lagune were previously exported to African and European countries and bred as Dahomey cattle, whereas the Somba contributed to the formation of two indigenous hybrids known as Borgou and Pabli cattle. These breeds are affected by demographic, economic, and environmental pressures in local production systems. Considering current and historical genomic data, we applied a formal test of admixture, estimated admixture proportions, and computed genomic inbreeding coefficients to characterize the five breeds. Subsequently, we unravelled the most recent selection signatures using the cross-population extended-haplotype homozygosity approach, based on the current and historical genotypes. Results from principal components analyses and high proportion of Lagune ancestry confirm the Lagune origin of the European Dahomey cattle. Moreover, the Dahomey cattle displayed neither indicine nor European taurine background, but they shared on average 40% of autozygosity from common ancestors, dated approximately eight generations ago. The Lagune cattle presented inbreeding coefficients larger than 0.13, however, the Somba and the hybrids (Borgou, Pabli) were less inbred (≤ 0.08). We detected evidence of admixture in the Somba and Lagune cattle, but they exhibited similar African taurine (AFT) ancestral proportion (≥ 96%) to historical populations, respectively. A moderate and stable AFT ancestral proportion (62%) was also inferred for less admixed hybrid cattle including the Pabli. In contrast, the current Borgou samples displayed lower AFT ancestral proportion (47%) than historical samples (63%). Irrespective of the admixture proportions, the hybrid populations displayed more selection signatures related to economic traits (reproduction, growth, milk) than the taurine. In contrast, the taurine, especially the Somba, presented several regions known to be associated with adaptive traits (immunity, feed efficiency). The identified subregion of BoLA class IIb (including DSB, BOLA-DYA) in Somba cattle is interestingly uncommon in other African breeds, suggesting further investigations to understand its association with specific adaptation to endemic diseases in Benin. Overall, our study provides deeper insights into recent evolutionary processes in the Beninese indigenous cattle and their aptitude for conservation and genetic improvement.